PATTERNS OF CHANGE OF TRIBOTECHNICAL PARAMETERS AND ACOUSTIC EMISSIONS SIGNALS FOR FRICTION PAIRS 30HGSA-D16 - Токарук, Віталій Володимирович; Мікосянчик, Оксана Олександрівна; Мнацаканов, Рудольф Георгійович; Кудрін, Анатолій Павлович (Problems of Friction and Wear, 2019)
Mechanisms of structural adaptability of contact surfaces with friction depending on hardness of coupled element in friction pair are considered. It is determined that the kinetics of the change in the average power of acoustic emission may establish the end of wear-in much earlier than in the case of change in the friction coefficient and the average temperature of the frictional contact. That indicates greater accuracy and less inertia of the measurement of wear-in period through the method of acoustic emission. It is defined that the reduction of wear-in due to the change in the average power of acoustic emission is due to the intensification of the mechano-physico-chemical processes under increasing temperature in the tribotechnical contact, which ensures the transition of the tribosystem to a state of structural adaptability with minimal energy dissipation. The investigated samples are characterized by a larger wear of a stationary triboelement in friction pairs. Weight deterioration of triboelements correlates with the parameter of the average power of acoustic emission both in the period of wear-in as well as in stable work of friction pairs.